Seven-year tobacco tax plan in Ukraine: a case study of the actors, tactics and factors motivating policy passage - Weiger, Caitlin; Hoe, Connie; Cohen, Joanna E. (BMJ open, 2022)
Objective In December 2017, the Ukrainian Rada passed legislation that would increase tobacco taxes for the next 7 years to meet requirements of the European Union-Ukraine Association Agreement (EU-UAA). We analysed factors motivating passage of Ukraine’s 7-year tobacco tax plan as well as tactics used by both opponents and proponents to describe how the plan was passed. - Design A case study approach was used. Data were gathered from semistructured interviews (n=12) and document review (n=24) and analysed using inductive and deductive coding. - Results The European Union-Ukraine Association Agreement, a significant budget deficit and a history of tobacco tax success were all contextual factors contributing to policy passage. Proponents of high tobacco taxes capitalised on this opportunity, using media advocacy, generating scientific evidence and collaborating effectively across multiple sectors to support the passage of the plan. Opponents used media advocacy and lobbied to water down several features of the plan, resulting in smaller increases that might not meet EU-UAA requirements. - Conclusion Industry interference via lobbying continues to hamper passage of high tobacco taxes and should be addressed via legislation that aligns with Article 5.3 of the Framework Convention on Tobacco Control. Proponents should look for windows of opportunity caused by external events, create a multisectoral coalition, including tax experts and use media advocacy to support tax increases. Further work should continue to document what contextual factors support tobacco control policy change.